Stem Diameter Growth of Scots Pine Trees after Increased Mechanical Load in the Crown during Dormancy and (or) Growth - LUNDQVIST, LARS; VALINGER, ERIK (Annals of Botany, 1996)
A field experiment with a 2 ×2 factorial block design (W x S x ) was conducted in northern Sweden where the mechanical loads in the crowns of sixteen 2.5m high Scots pine ( Pinus sylvestris L.) trees were increased during one winter (W 1 , dormant period) and (or) summer (S 1 , growth period). Trees treated were loaded with five 2kg bags hung over mid-crown branches close to the stem, i.e. 10kg per tree. After treatment, all trees were left to grow untreated for one additional year. Trees were then cut at ground level and annual ring widths for the last 5 years were measured on stem discs taken at 1, 5, 10, 15, 20, 30 and 50% of tree height. Differences between treatments were analysed with two-way factorial ANOVA. Accumulated treatment response was positive for winter loading (W 1 S x ) at all levels, and statistically significant at 1, 15 and 20% of tree height. Summer loading (W x S 1 ) had positive effects at the lowest and middle parts of the stem, and negative in between. No statistically significant two-way interaction (W ×S) was observed. Results support the hypothesis that Scots pine trees can retain information about mechanical forces acting on their stems during winter, and respond to this during the following growth period. The results also suggest that stem form of trees in boreal forests may be strongly affected by winter conditions.